A meta‐analysis of the association between Helicobacter pylori infection and risk of atherosclerotic cardiovascular disease. Issue 6 (7th October 2020) - Wang, Bin; Yu, Mingyang; Zhang, Rongguang; Chen, Shuaiyin; Xi, Yuanlin; Duan, Guangcai
Abstract: Background: Helicobacter pylori ( H pylori ) infection may be a risk factor for cardiovascular disease (CVD), but the reported researches have given conflicting results. Aims: To investigate the association between H pylori infection and risk of atherosclerotic CVD. Materials and Methods: The studies were retrieved in Embase, PubMed, Web of Science (published from Jan 1, 1990, to Jan 31, 2020, language restrictions: English). All studies included used data from case‐control studies and cohort studies of cardiovascular adverse events. Random effect models were used to measure pooled estimates. All data were analyzed with Stata 11.2 SE (StataCorp, College Station, TX). Results: Helicobacter pylori infection increased the risk of adverse cardiovascular events by 51% (40 studies, n = 19 691, odd ratio [OR] = 1.51, 95% confidence interval [CI]: 1.34‐1.70). The effect was greater for studies that the type of CVDs was myocardial infarction (MI) and cerebrovascular disease (MI OR = 1.80, 95% CI: 1.42‐2.26, cerebrovascular disease OR = 1.54, 95% CI: 1.27‐1.89). Meanwhile, CagA seropositive H pylori strains were associated with a significantly increased risk of cardiovascular adverse events based on published research data (OR = 1.73, 95% CI: 1.40‐2.14). Conclusion: In conclusion, H pylori infection enhanced the risk of atherosclerotic cardiovascular adverse events, especially in some patients with MI and cerebrovascular disease. This study will provide guidance for the targeted prevention and treatment of CVDs. But this association need to be confirmed by more prospective studies.